Field-Driven Language Learning: Exploring Emotional Intelligence and Autonomy in Indonesian EOP Programs - Ratni, Ni Putu; Dollah, Syarifuddin; Basri, Muhammad (Universitas Lancang Kuning, 2025)
Autonomous learning has emerged as a crucial pedagogical approach for equipping students with the skills necessary to thrive in dynamic, communication-driven industries such as tourism. However, limited research exists on the implementation of autonomous English language learning through field-based practices within Indonesian religious-affiliated universities. This study examines the practice of Autonomous Learning (AL) among students in the Travel Industry Study Program at Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar through a collaborative field study conducted with international students from the SIT Program. Grounded in Humanistic Learning Theory and Emotional Intelligence frameworks, this mixed-methods research investigates three core objectives: the implementation of AL in English learning, indicators of autonomy within the learning process, and the emotional impact on learners. Data were gathered through literature documentation, a student survey, and data triangulation involving program reports, academic references, and participant responses. The findings reveal that AL was effectively fostered through student-centered, collaborative field experiences that encouraged self-direction, intrinsic motivation, and emotional engagement. Despite moderate self-awareness and vocabulary limitations, students exhibited positive emotions such as joy and increased self-esteem, validating the affective benefits of the program. This study contributes to the discourse on learner autonomy by demonstrating how humanistic and experiential learning environments can bridge linguistic, cultural, and psychological gaps. It advocates for institutional support in re-establishing collaborative programs and integrating AL practices into EOP (English for Occupational Purposes) pedagogy, thereby offering a model adaptable to similar educational contexts across Indonesia and beyond.